Integrating the health.moves.minds. Program into PETE. Issue 5 (12th June 2020) - Linker, Jenny M.; Deutsch, Joe
Abstract : Using whole child approaches and promoting the development of social and emotional learning skills are educational priorities in today's K-12 schools. SHAPE America's heath.moves.minds. program helps school and community personnel address these priorities via movement-based lessons. PETE faculty can address several national standards and competencies by embedding this new curriculum and fundraiser within their existing curriculum while fostering teacher candidates' knowledge and skills to address whole school approaches in their future career settings. This article describes how faculty at one PETE institution has progressively integrated heath.moves.minds. throughout its program.